(untitled) (Universal International Scientific Journal, 2026)
.This article analyzes the content and essence of information attacks in the context of globalization and digital transformation, their psychological and social impact on the minds of young people on a scientific basis. The theoretical foundations of the concept of spiritual and moral immunity are highlighted, and the role of family psychology in its formation is revealed. Also, the impact of gender stereotypes on child upbringing, socialization of the individual and the formation of social consciousness is considered on the basis of a comprehensive approach. During the study, the issues of media literacy, critical thinking, social control mechanisms and pedagogical cooperation are widely covered, and practical proposals and recommendations are developed